Design and Development of a Mobile Plastic Paving Block Unit for the Revitalization of the Parking Area at the Faculty of Engineering, Universitas Graha Nusantara Padangsidimpuan - Ahmad Rafii (SEAN Institute, 2026)
Pavement damage and standing water in the parking area of the Faculty of Engineering, Universitas Graha Nusantara (UGN) Padangsidimpuan indicate that sustainable infrastructure principles have not yet been optimally applied in the revitalization of campus facilities, while the national plastic-waste recycling rate remains low. This study aims to analyze the existing condition of the pavement, examine the potential of plastic waste as an environmentally friendly paving-block material, and design a mobile plastic paving-block unit that is technically feasible for revitalizing the parking area. The study employs an engineering-based research approach at Technology Readiness Level (TRL) 3, drawing on field observation, compressive-strength and water-absorption testing of four polypropylene (PP) plastic-waste mix compositions, and functional testing of the mobile-unit prototype across five production batches. The results show that the existing pavement damage ratio reaches 34.0% of the total parking area, dominated by standing water and alligator cracking. The PP:sand 60:40 composition yields a compressive strength of 15.6 MPa and a water absorption of 2.1%, satisfying SNI 03-0691-1996 Grade C for pedestrian walkways and two-wheeled-vehicle parking, but not yet meeting Grade B for four-wheeled-vehicle parking. The mobile unit achieved an average production efficiency of 87.2%, rising from 76% in the first batch to 92% in the fifth. This study contributes an integration of plastic-waste-based material innovation with a mobile, field-deployable production system, distinct from conventional approaches that remain static and laboratory-oriented, and provides a foundation for advancing to the next technology readiness stage.